-3x-5(x+3)=-(1+x)

Simple and best practice solution for -3x-5(x+3)=-(1+x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3x-5(x+3)=-(1+x) equation:


Simplifying
-3x + -5(x + 3) = -1(1 + x)

Reorder the terms:
-3x + -5(3 + x) = -1(1 + x)
-3x + (3 * -5 + x * -5) = -1(1 + x)
-3x + (-15 + -5x) = -1(1 + x)

Reorder the terms:
-15 + -3x + -5x = -1(1 + x)

Combine like terms: -3x + -5x = -8x
-15 + -8x = -1(1 + x)
-15 + -8x = (1 * -1 + x * -1)
-15 + -8x = (-1 + -1x)

Solving
-15 + -8x = -1 + -1x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add 'x' to each side of the equation.
-15 + -8x + x = -1 + -1x + x

Combine like terms: -8x + x = -7x
-15 + -7x = -1 + -1x + x

Combine like terms: -1x + x = 0
-15 + -7x = -1 + 0
-15 + -7x = -1

Add '15' to each side of the equation.
-15 + 15 + -7x = -1 + 15

Combine like terms: -15 + 15 = 0
0 + -7x = -1 + 15
-7x = -1 + 15

Combine like terms: -1 + 15 = 14
-7x = 14

Divide each side by '-7'.
x = -2

Simplifying
x = -2

See similar equations:

| -18-4y-y=13 | | -6c-4-5c= | | 9(x-3)=-27+9x | | 2x-57= | | -5u-2=3u^2 | | 5x+6=x+4 | | (x+20)+(210-3x)+x=180 | | 0.9(6x+12)=1.6-(x+2) | | 4n+3n=21 | | 2d+7+3d=-41 | | 2.5y+8= | | 2x+8=38+5x | | 4+2a=3(s-2)+1 | | 1.9(g-9.1)=-7.22 | | .5j=5 | | 11.54-d=6.54 | | 15.8=1.2(r-4)+9.8 | | 8x^2=4-7x | | 6=-4-2 | | 6+6x(x+8)= | | 5(9-11)=m-8 | | 2y=2y+40 | | -k+3=-4 | | 8m=-64 | | 4y+40=10y-20 | | U^2=15u+36 | | 21-42=3(x-2)-6 | | -2+8+n=-7+9 | | 2y-4x=8forx | | -2+8=-7+9 | | 10c^2-8c= | | 4x+20=48 |

Equations solver categories